Analisis Sistem Kompensasi Ukm Xyz Kota Bekasi Dengan Pendekatan Adhered Dan Overlapping - Aurellia Azzahra; Diajeng Siti Aqiilah Sundari; Kartika Kusumawati; Sofiyah Sofiyah; Widyawati Widyawati; Lindawati Kartika (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
SMEs face various challenges because human resources are the main asset in their operations. One important aspect of human resource management is appropriate compensation. SME XYZ is an SME engaged in the food and beverage (F&B) sector. This study evaluates the compensation system at SME XYZ. The methods used for evaluating the compensation system at SME XYZ are the adhered method and the overlapping method. This research is expected to provide new insights for SME XYZ owners in Bekasi City as an evaluation material for their compensation system. Based on the calculations of both methods, it is found that the compensation at SME XYZ is currently considered ideal as it falls within the specified range and meets the criteria